Edukasi Interaktif Pencegahan Stunting untuk Ibu Hamil di Puskesmas Poka–Rumah Tiga Ambon: Interactive Education on Stunting Prevention for Pregnant Women at Poka–Rumah Tiga Health Center, Ambon - Tando, Yudhie Djuhastidar; Titaley, Christiana Rialine; Que, Bertha Jean; Taihuttu, Yuniasih Mulyani Jubeline; Angkejaya, Ony Wibriyono; Oetama, Evan Christian; Liyani Sartika Sara; Siwtiory, Ezra Puthrien A. (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Stunting, a form of growth and development impairment due to chronic undernutrition, is a major threat to the quality of human resources. Faculty of Medicine, Pattimura Unversity Ambon, conducted a health education activity aimed at increasing the knowledge of pregnant women and their husbands regarding the importance of efforts to prevent stunting since the pregnancy period. This activity was carried out on 21 December 2021 involving 55 participants consisting of pregnant women and their husbands living in the catchment area of ​​the Poka-Rumah Tiga Health Center, Ambon City. The activity included: 1) Provision of educational materials from resource persons 2) Evaluation of participant knowledge (pre and post-test), and 3) Distribution of promotional media (leaflets) to participants. This activity received positive responses from the Ambon City Health Office, Poka-Rumah Tiga Health Center, and all participants who attended the training. The pre-test assessment before the education sessions showed that 2% of participants had a 'low' level, 45% had a 'moderate' level and 53% had a 'high' level of knowledge about stunting and its prevention. However, in the post-test assessment after the end of the education session, none had a 'low' level of knowledge, only 25% had a ’moderate’ level and 75% of participants had a 'high' level of knowledge. The results indicated an increased level of knowledge in pregnant women and their husbands about the importance of stunting prevention since pregnancy after the training. This educational activity could be carried in the future by involving pregnant women in other areas in Ambon City.